Gestão do conhecimento e ergonomia cognitiva: relações na criação e no reúso do conhecimento em contextos capacitantes - Trevisan, Edu Rosa (2020)
Knowledge Management advocates for the creation and reuse of active knowledge in environments that provide interaction between the actors involved, the enabling contexts or bas. Cognitive Ergonomics studies the relationship between human beings and interaction environments, from the view to making them healthy, favoring decisionmaking processes. The present dissertation sought to demonstrate the existence of a descriptive correlation between Knowledge Management and Cognitive Ergonomics treated in the academic literature, in medium and large companies in the Brazilian industrial segment that enable the creation and reuse of knowledge from the perspective of the SECI model, in these interaction places. From a bibliographic research with content analysis, supported by the using of the MaxQda tool, it was identified, then, that there are relationships and connections that would make ergonomic industrial environments effective, in the creation and reuse of knowledge from the perspective of the SECI model. The results, after interpretation of the content analysis and the thematic approach exposed in the conceptual alignment, however, made it possible to infer that the literature does not explicitly evidence the thematic correlation sought, but there is an explicit relationship between ergonomically healthy environments and the enabling context, necessary for the creation and reuse of knowledge, evidenced by the existence of terminological co-occurrence. The existence of this explicit connection between enabling contexts and healthy environments opens the prospect of a real approximation between Knowledge Management and Cognitive Ergonomics in industrial environments and their related territories.